Kedudukan Anak Angkat Dalam Harta Warisan Terhadap Perspektif Hukum Islam dan Hukum Positif - Muhamad Wahyudin (Formosa Journal of Sustainable Research, 2022)
Adoption of a child is a problem that occurs in a family, and in Indonesia itself there are many conflicting issues regarding the division of inheritance and lineage of adopted children and how the legal procedures are listed in Islamic Law and Positive Law. This type of research is qualitative or field research, because the sources of data needed to compose this thesis are one or several informants who provide information directly through interviews. The results obtained in the practice of obtaining adopted children that occur in the community and the position of adopted children against inheritance according to Islamic law and positive law.